Konsep Tasawuf dalam Perspektif Konseling Islami - Abdul Aziz; Randi Saputra (Guidance : Jurnal Bimbingan dan Konseling, 2022)
This paper aims to describe the concept of Sufism in the view of Islamic counseling. Indeed, Islamic counseling departs from the general concept of the discipline of guidance and counseling which realizes that everyone has a basic footing who wants a peaceful, safe and happy life. However, every human being does not escape the problems of life he faces and needs professionals when the problems they face cannot be solved. This research was conducted qualitatively by means of a literature review. The conclusion of the study is the concept of Sufism such as Muraqabah (feeling the presence of Allah SWT in all conditions), Mahabbah (love for Allah SWT exceeds love for His creatures), Khawf (fear of fear of committing sins) and Syawq (extraordinary love for God). Allah SWT).